Oral manifestations arising from eating disorders and the importance of the multidisciplinary approach (Research, Society and Development, 2021)
Eating disorders are behavioral conditions that negatively interfere with the general health and well-being of an individual, with Anorexia Nervosa and Bulimia Nervosa being the most common disorders. Eating disorders manifest themselves in a systemic way due to compromised nutritional status and the same occurs in the oral cavity. Given the above, this article aims to review the literature on oral health in patients who have eating disorders and point out which are the most common oral manifestations in these patients. For the construction of this article, a bibliographic survey was carried out in the Latin American and Caribbean Literature in Health Sciences (LILACS), Scientific Electronic Library Online (Scielo) and US National Library of Medicine (PUBMED) databases. the years 2010 to 2021. The bibliographic survey revealed that the most common oral manifestations in patients who have some type of eating disorder are dental erosion, caries disease, dentinal sensitivity and xerostomia. cause of oral lesions. The health team must include, in addition to dentists, physicians, nutritionists, psychologists and, in some cases, the psychiatrist, in order to prevent future damage to health and ensure the patient's general well-being.